PENDEKATAN GENDER: KEPEMIMPINAN PEREMPUAN DALAM PRESPEKTIF ISLAM - nadhifah, kholifia (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Gender issues have many problems, one of which is gender inequality which causes a lot of debate among society, where women are often disadvantaged. This research aims to answer various kinds of problems regarding gender equality. This research is qualitative research with a library research type of research and the analysis used uses comparative analysis by comparing events directly or with literature. Research result; 1) Gender is something within humans that is created unnaturally, can be changed, can be created and created by a society. Sex is something that exists from birth, is given by God, is natural and cannot be changed. 2) Gender equality is the existence of equality between men and women in gaining access, participation, control and benefits in all activities. Meanwhile, gender justice is a process towards equality. 3) Three forms of studies that examine gender in Islamic studies, namely; research that starts from pure studies, research that starts from studies of social science and humanities approaches, research that starts from studies that map gender issues.